Haron Din gets posthumous award - News Straits, Times (New Straits Times, 2016)
SERDANG: The late Pas spiritual leader Datuk Dr Haron Din was posthumously conferred the "Maal Hijrah Special Award", while former chief justice Tun Dr Ahmad Fairuz Sheikh Abdul Halim was named "Tokoh Maal Hijrah" yesterday.